The Impact of Macroprudential Policy on Credit Growth in Nine Euro Area Economies - Eva Lorenčič; Robert Volčjak; Mejra Festić (Naše gospodarstvo/Our economy, 2023)
In this paper, we investigate the impact of macroprudential policy measures (bundled together into a macroprudential policy index, MPI) on the non- financial corporate sector credit and household credit growth using a one-step system GMM empirical research method. The goal of our paper is to test whether contractionary macroprudential policy stymies credit growth rate and whether expansionary macroprudential policy spurs credit growth rate in selected Euro Area economies (Austria, Belgium, Finland, Germany, Ireland, Italy, Netherlands, Slovenia, and Spain) over the period 2008Q4–2018Q4. We test two hypotheses: H1: The tightening of macroprudential policy measures reduces the non-financial corporate sector credit growth rate, and H2: The tightening of macroprudential policy measures reduces the growth rate of household credit. Based on our empirical results, we can confirm the first hypothesis. In contrast, the second hypothesis can be neither confirmed nor rejected since the explanatory variable of interest (MPI) is statistically insignificant in the second model.